Rancang Bangun Sistem Informasi Pengaduan Orang Hilang Menggunakan Mobile Phone Dengan Metode Waterfall (Studi Kasus:Kapolsek Babelan Bekasi Utara) - Fatiha Khoirunisa; Estu Sinduningrum (Prosiding Seminar Nasional Teknoka, 2020)
Information systems are a combination of technology and the activities of the people who use them. Information systems can support operations and management which refers to interactions between people, algorithmic processes, data and technology. The purpose of this research is to make it easier for people to find lost family and relatives. The number of people missing and complaints to thepolice in the Babelan area of North Bekasi is overwhelming because they are still using manual methods, only distributed through social media. The police only ask for complaints manually and spread directly through social media. Without any information stored on the reporting party, most of the people get the information report for only a short period of time without knowing any further developments (updates) from the missing person's complaint. This study uses the waterfall method with several phases, namely requirements analysis, system design, implementation and testing. Illustrates the basic concepts of an Android-based information system consisting of input, model, output, technology, hardware, and software. The results obtained from testing in this study 85.50% stated that the application has met the ideal score of the software. The information system for missing persons complaints based on android is very helpful in finding the whereabouts of missing family and relatives.